Charge‐Tagged N‐Heterocyclic Carbenes (NHCs): Revealing the Hidden Side of NHC‐Catalysed Reactions through Electrospray Ionization Mass Spectrometry. Issue 2 (30th November 2020) - Salvitti, Chiara; Chiarotto, Isabella; Pepi, Federico; Troiani, Anna
Abstract: N ‐heterocyclic carbenes (NHCs) are key intermediates in a variety of chemical reactions. Owing to their transient nature, the interception and characterization of these reactive species have always been challenging. Similarly, the study of reaction mechanisms in which carbenes act as catalysts is still an active research field. This Minireview describes the contribution of electrospray ionization mass spectrometry (ESI‐MS) to the detection of charge‐tagged NHCs resulting from the insertion of an ionic group into the molecular scaffold. The use of different mass spectrometric techniques, combined with the charge‐tagging strategy, allowed clarification of the involvement of NHCs in archetypal reactions and the study of their intrinsic chemistry. Abstract : A charge‐tagging strategy has been successfully applied to investigate the chemistry of N ‐heterocyclic carbenes (NHCs) in the gas phase. These neutral species, intrinsically invisible to mass spectrometry, become detectable by the insertion of a positive‐ or negative‐charged group into the molecular scaffold, allowing their isolation from the reaction mixture and mechanistic elucidation of archetypal NHC‐catalysed processes.